2022
DOI: 10.3389/fpsyg.2022.812831
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Non-cohabiting Relationships and Changes in Life Satisfaction and Mental Health

Abstract: This study investigates how individuals’ life satisfaction and depression are affected by the dissolution of a steady non-cohabiting intimate relationship. Previous studies have focused more on the consequences of divorce and less on the influence of non-cohabiting relationships on the well-being of the individual. The data for this study were taken from pairfam, a large-scale German panel survey, and were used to estimate fixed-effects panel regression models and impact functions to identify the overall effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…For separation, some studies reported increases in extraversion (Neyer & Lehnart, 2007), agreeableness (Bühler et al, 2022; Specht et al, 2011b), and openness (Specht et al, 2011b), while other studies found no change in Big Five personality traits (Asselmann & Specht, 2020; Denissen et al, 2019; Neyer & Asendorpf, 2001; Pusch et al, 2019). Separation has also been associated with a decline in self-esteem, which mainly applied to the dissolution of a relationship longer (vs. shorter) than 1 year (Luciano & Orth, 2017), and a decline in life satisfaction (Preetz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For separation, some studies reported increases in extraversion (Neyer & Lehnart, 2007), agreeableness (Bühler et al, 2022; Specht et al, 2011b), and openness (Specht et al, 2011b), while other studies found no change in Big Five personality traits (Asselmann & Specht, 2020; Denissen et al, 2019; Neyer & Asendorpf, 2001; Pusch et al, 2019). Separation has also been associated with a decline in self-esteem, which mainly applied to the dissolution of a relationship longer (vs. shorter) than 1 year (Luciano & Orth, 2017), and a decline in life satisfaction (Preetz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, more studies on the potential long-term effects on life satisfaction resulting from returns to the parental home are needed. Individuals adapt to major life-course events, and changes in life satisfaction often show a rapid adjustment to baseline levels [ 84 , 85 , 86 ]. After an initial decrease in life satisfaction, young adults could adjust to their new living arrangement when challenges and conflicts between parents and returnees decline over time.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in the context of divorce, set-point theory and related evidence suggest that the emotional distress brought about by the relationship’s dissolution dissipates within 5 years (Asselmann & Specht, 2022a, 2022b). In some cases, the years following separation are characterized by improved mental health in absolute, and not merely relative, terms (Preetz, 2022). This suggests that individuals largely find ways to cope with and adapt to divorce-induced distress, and that this process takes place in the time frame of years.…”
Section: Breakups Distress and Recovery In Young Adults: Unanswered Q...mentioning
confidence: 99%